Pierre Verger : um outro olhar sobre o sertanejo na revista O Cruzeiro (1946-1951) - Costa, Ialê Menezes Leite (2015)
This research aims to identify another respective regarding the sertanejo figure in the magazine called O Cruzeiro (1946-1951) through Pierre Verger´s photo reports. We intend to analyze Verger´s angle in the pages of O Cruzeiro, whose works compound the moment of formation of this journal´s new visual identity, also analyzing different connected visual languages as well as considering mainstream ideas at that time in a vast context. It hasn´t been given importance to his participation in this magazine, what makes it significant to be recovered by us: the historical dimension of his work in the Brazilian photojournalism formation. The Brazilian photojournalism formation has been seen as a formulator of speeches concerning our culture, being able to attribute meanings to the construction of Northeast identity and its population. This study was made of qualitative analysis of photo reports, where we tried to understand how the construction of different viewpoints on sertanejo´s representation was done in the magazine O Cruzeiro. We believe that Verger has given other prospect at this "national stereotype", composing unusual imagery narratives in the context of visual culture proposed by the journal, along with differing in relation to the recurrence of other stigmatizing discourses, although he´s also contributed to the association between the categories "Northeast "and" past ".